Lost in a house of mirrors: Journalists come to terms with myth and reality in The Newsroom. (August 2015) - Koliska, Michael; Eckert, Stine
The first season of the television drama The Newsroom drew predominantly negative critiques by journalists. A textual analysis of The Newsroom 's first season and more than 90 articles in US news media about that season showed that journalists rejected the idealistic depiction of the journalism profession. Applying new institutional theory and the concepts of decoupling/coupling, we argue journalists criticized such a depiction because it clashed with their own institutional myth that is understood to legitimize journalism to the broader public. Journalists' mostly negative responses were an attempt to rhetorically restore this myth by decoupling it from journalistic practice.